Therapeutic Nuclear Medicine - Baum, Richard P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The recent revolution in molecular biology offers exciting new opportunities for targeted radionuclide therapy. The selective irradiation of tumor cells through molecular biological mechanisms is now permitting the radiopharmaceutical control of tumors that are unresectable and unresponsive to either chemotherapy or conventional radiotherapy. In this up-to-date, comprehensive book, world-renowned experts discuss the basic principles of radionuclide therapy, explore in detail the available treatments, explain the regulatory requirements, and examine likely future developments. The full range of clinical applications is considered, including thyroid cancer, hematological malignancies, brain tumors, liver cancer, bone and joint disease, and neuroendocrine tumors. The combination of theoretical background and practical information will provide the reader with all the knowledge required to administer radionuclide therapy safely and effectively in the individual patient. Careful attention is also paid to the important role of the therapeutic nuclear physician in delivering the effective coordination of a diverse multidisciplinary team that is essential to the safe provision of treatment.
PART I: Basic Principles (11 chapters) -- PART II: Clinical Applications: Brain and Nasopharyngeal Tumors (4 chapters).-Thyroid Cancer (11 chapters) -- Benign Thyroid Diseases (2 chapters) -- Primary and Metastatic Liver Cancer (5 chapters) -- Bone and Joint Disease (5 chapters) -- Hematological Malignancies (8 chapters) -- Endocrine Tumors (2 chapters) -- Radioimmunotherapy (7 chapters) -- Intravascular/Intracavitary/Interstitial and Epidemal RadionuclideTherapy (5 chapters) -- PART III: Radiation Biology and Dosimetry (11 chapters) -- PART IV: Radiation Planning and Perspectives of Radionuclide Therapy (10 chapters) -- Subject Index.
Keywords: Radiology; Nuclear medicine; Oncology .; Imaging / Radiology; Nuclear Medicine; Oncology